The Impact of Tax Policy on The Growth of Micro, Small, And Medium En-terprises (MSMEs) In Indonesia - Kertojoyo, Goei Elvian (IHSA Institute, 2024)
Micro, Small, and Medium Enterprises (MSMEs) contribute significantly to the Indonesian economy, accounting for 60% of GDP and 97% of jobs. However, this sector still faces challenges in taxation, particularly related to administration and tax burden. The government has implemented a final income tax policy of 0.5% as an effort to support MSMEs. The research uses a combination of normative juridical and qualitative empirical methods, with data collection through literature study, interviews with 30 MSME actors, surveys of 200 respondents, observation, and Focus Group Discussion. The research findings reveal that although tax policies have simplified the tax system for MSMEs, their implementation is still hindered by low levels of tax compliance and understanding. There is a need for policy refinement that is oriented towards the needs of MSMEs, as well as more intensive education and mentoring programs to support the growth of this sector